Multi-wavelength Brillouin Raman erbium-doped fiber laser generation in a linear cavity - Shirazi, M.R.; Harun, Sulaiman Wadi; Ahmad, Harith (IOP Publishing, 2014)
A multi-wavelength Brillouin Raman erbium-doped fiber laser is proposed and demonstrated. The setup uses a 7.7 km dispersion compensating fiber simultaneously as the Brillouin and Raman nonlinear gain media and operates in conjunction with a 3 m erbium-doped fiber as the linear gain medium. At a Brillouin pump (BP) wavelength of 1530 nm, where Raman and erbium gains overlap each other, 34 Brillouin Stokes lines having line spacing of 0.075 nm are created by using a Raman pump power of only 24.1 dBm, an erbium pump power of about 22.1 dBm, and a BP power of 6.5 dBm in the proposed linear cavity. The system is highly efficient and is able to generate many comparable peak-power lines at a low pump power.